Formulation of toro tuna-based instant porridge with addition of seaweed flour for baby complementary food: Formulasi bubur instan berbasis toro tuna dengan penambahan tepung rumput laut untuk makanan pendamping ASI - Ukhty, Nabila; Khairi, Ikhsanul; Akbardiansyah, Akbardiansyah (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2025)
The high incidence of malnutrition among children under five in Indonesia underscores the critical need for timely and comprehensive interventions to mitigate its impact. One of the factors contributing to malnutrition in toddlers is a lack of balanced nutrition in complementary food (CF). Fishery commodities such as tuna and seaweed have great potential to be developed into instant complementary food porridge for complementary feeding because they contain amino acids and essential fatty acids that toddlers need for brain and eye development. This research aimed to determine the best formulation for instant MPASI porridge made from toro tuna fish and seaweed flour based on organoleptic assessment, fatty acid profile, and amino acid profile. The complementary food porridge with toro tuna and seaweed flour consists of four treatments, namely 94%:6%, 88%:12%, 82%:18%, and 76%:24%. The parameters analyzed included sensory tests (appearance, color, taste, and texture), fatty acid profile, and amino acid profile. Based on the research results, the differences in the formula of toro tuna and seaweed flour influence the panelists' level of preference for appearance, smell, and taste parameters. Organoleptic evaluation selected the formula with a ratio of 82%:18% as the best. The dominant fatty acids include palmitic acid (SFA) at 33.68%, oleic acid (MUFA) at 45.95%, and linoleic acid (PUFA) at 1.34%. The dominant essential amino acid is leucine at 1.28%, and the dominant non-essential amino acid is glutamic acid at 1.37%. Toro tuna and seaweed flour can be utilized in the production of instant complementary feeding porridge.